2014
DOI: 10.3389/fnbeh.2014.00358
|View full text |Cite
|
Sign up to set email alerts
|

An fMRI study on the influence of sommeliers' expertise on the integration of flavor

Abstract: Flavors guide consumers' choice of foodstuffs, preferring those that they like and meet their needs, and dismissing those for which they have a conditioned aversion. Flavor affects the learning and consumption of foods and drinks; what is already well-known is favored and what is new is apprehended. The flavor of foodstuffs is also crucial in explaining some eating behaviors such as overconsumption. The “blind” taste test of wine is a good model for assessing the ability of people to convert mouth feelings int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
29
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 89 publications
(149 reference statements)
2
29
0
Order By: Relevance
“…Several nodes, such as the olfactory cortex, insula, amygdala, parahippocampal gyrus, operculum, and putamen, have been associated with processing odor identification and gustatory and sensory networks in earlier studies (Castriota-Scanderbeg et al, 2005;Pazart et al, 2014;Royet et al, 2013). Our results also include significant functional alterations in brain regions (precuneus, caudate, and putamen) involved in high-level cognition network (e.g., attention, mental imagery, working memory).…”
Section: Effective Connectivity Differences Between Sommeliers and Cosupporting
confidence: 60%
See 1 more Smart Citation
“…Several nodes, such as the olfactory cortex, insula, amygdala, parahippocampal gyrus, operculum, and putamen, have been associated with processing odor identification and gustatory and sensory networks in earlier studies (Castriota-Scanderbeg et al, 2005;Pazart et al, 2014;Royet et al, 2013). Our results also include significant functional alterations in brain regions (precuneus, caudate, and putamen) involved in high-level cognition network (e.g., attention, mental imagery, working memory).…”
Section: Effective Connectivity Differences Between Sommeliers and Cosupporting
confidence: 60%
“…For example, neural correlates of performance in archers (Kim et al, 2014), altered insula activation in expert meditators (Lutz et al, 2013), distinct patterns of olfactory regions and hippocampus activation in perfumers when imaging smell (Plailly et al, 2012) and, during wine tasting, a functional magnetic resonance imaging (fMRI) study showed that wine experts (sommeliers) showed increased activation of the memory network (Pazart et al, 2014).…”
mentioning
confidence: 99%
“…Therefore, even though cognitive processing is primordial [1,2], the emotion caused by wine tasting is above all due to direct contact between wine stimuli and the taster's sensory receptors. These stimuli are volatile and non-volatile compounds that are responsible for the odors and tastes of wine, respectively.…”
Section: Introductionmentioning
confidence: 98%
“…Pazart et al ( 2014 ) designed an fMRI study to describe the differences in brain activation in wine experts compared to control subjects. They observed specific areas activated in the experts' brains during all phases of wine tasting and reported that wine experts showed a more immediate and targeted sensory reaction to wine stimulation than control subjects.…”
Section: Human Odor Memory and Perceptionmentioning
confidence: 99%